Study of mitochondrial respiratory defects on reprogramming to human induced pluripotent stem cells - Hung, Sandy S C; Van Bergen, Nicole J; Jackson, Stacey; Liang, Helena; Mackey, David A; Hernández, Damián; Lim, Shiang Y; Hewitt, Alex W; Trounce, Ian; Pébay, Alice; Wong, Raymond C B (Aging (Albany, NY.), 2016)
Reprogramming of somatic cells into a pluripotent state is known to be accompanied by extensive restructuring of mitochondria and switch in metabolic requirements. Here we utilized Leber's hereditary optic neuropathy (LHON) as a mitochondrial disease model to study the effects of homoplasmic mtDNA mutations and subsequent oxidative phosphorylation (OXPHOS) defects in reprogramming. We obtained fibroblasts from a total of 6 LHON patients and control subjects, and showed a significant defect in complex I respiration in LHON fibroblasts by high-resolution respiratory analysis. Using episomal vector reprogramming, our results indicated that human induced pluripotent stem cell (hiPSC) generation is feasible in LHON fibroblasts. In particular, LHON-specific OXPHOS defects in fibroblasts only caused a mild reduction and did not significantly affect reprogramming efficiency, suggesting that hiPSC reprogramming can tolerate a certain degree of OXPHOS defects. Our results highlighted the induction of genes involved in mitochondrial biogenesis (TFAM, NRF1), mitochondrial fusion (MFN1, MFN2) and glycine production (GCAT) during reprogramming. However, LHON-associated OXPHOS defects did not alter the kinetics or expression levels of these genes during reprogramming. Together, our study provides new insights into the effects of mtDNA mutation and OXPHOS defects in reprogramming and genes associated with various aspects of mitochondrial biology.